Don Luigi Sturzo. A Man Through Many Seasons - Giovanna Farrell-Vinay (Revista de História da Sociedade e da Cultura)
In 1891 Rerum Novarum led a Sicilian priest, Luigi Sturzo (1871-1959), towards Christian democracy. In 1919 he founded the Partito Popolare Italiano, a mass party. Italian Catholics entered national politics amid great instability. Fascism quashed the Popolari and the Vatican settled the Roman Question with Mussolini, sending Sturzo into exile. He lived in London from October 1924 to September 1940, when he moved to the US. He returned home in 1946. Aided by British Liberal intellectuals, Labourists and progressive Catholics, he established himselfas a scholar, political moralist and leading anti-Fascist. His US secret mission, agreed with British Intelligence to overturn Catholic isolationism, was partly wrecked by Italian diplomats and Catholic prelates who relegated him to Jacksonville. But St. Augustine's Bishop, Joseph Hurley, protected him. Sturzo co-operated with Hurley and with British and American Intelligence, first against Nazism, then against Communism. He prepared the ground for the post-war success of De Gasperi's Democrazia Cristiana, but back home became its fiercest critic.